Economical and Biological Characteristic of the Variety Samples of Spring Wheat with Different Geographical Provenance - Л. М. Голик (Plant Varieties Studying and Protection)
Results of the spring wheat of different ecotype variety samples research by economical and biological feature have been reflected, and more valuable samples, which we have used during the breeding with the aim of new varieties creation, have been selected